2021
DOI: 10.3390/antibiotics11010046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Polyphenols and Natural Polyphenolic Extracts on Clinical Isolates

Abstract: Antibiotic resistance is a growing global problem that affects people, animals, the environment, and the economy. Many clinically relevant bacteria have become resistant to antibiotics, and this fact is emerging as one of the major threats to public health. The lack of new antibiotics, which is due to their time-consuming and costly development, exacerbates the problem. Therefore, it is necessary to identify new antimicrobial agents to treat bacterial and fungal infections. Plant extracts, which are valuable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 34 publications
1
71
0
1
Order By: Relevance
“…[45] showed that flavonoids have significant antifungal properties against Candida spp. As polyphenols have powerful antibacterial properties, they could be crucial in a new approach to treating pathogenic microbes [46,47]. Alkaloids as well exhibit significant antibacterial activities against pathogenic microbial strains [48].…”
Section: Antimicrobial Activity Of S Elaeagnifolium Hydro-ethanolic E...mentioning
confidence: 99%
“…[45] showed that flavonoids have significant antifungal properties against Candida spp. As polyphenols have powerful antibacterial properties, they could be crucial in a new approach to treating pathogenic microbes [46,47]. Alkaloids as well exhibit significant antibacterial activities against pathogenic microbial strains [48].…”
Section: Antimicrobial Activity Of S Elaeagnifolium Hydro-ethanolic E...mentioning
confidence: 99%
“…As presented by Caniça et al [ 3 ], the co-circulation of commensal and pathogenic bacteria in different reservoirs enables the spreading of resistance and the rapid emergence of multidrug-resistant strains. While the lack of new antimicrobials exacerbates the problem, it is necessary to identify new agents for therapeutic strategies against AR [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of multidrug-resistant bacteria is a grave issue that is responsible for prolonged infections and treatment failures. The majority of nosocomial infections now comprise of six resistant pathogenic isolates that have been grouped together as ESKAPE by the Infectious Disease Society of America ( Manso et al 2021 ). These include Enterococcus faecium, S. aureus, K. pneumoniae, Acinetobacter, P. aeruginosa and Enterobacter species.…”
Section: Discussionmentioning
confidence: 99%